Assessment of unhealthy days of urban marginal inhabitants and effective factors in Mashhad, Iran - Maliheh Ziaee; Lida Jarahi; Mohammad Khajedaluee; Ehsan Taghian (Social Determinants of Health, 2016)
Background: The concept of the quality of life (HRQOL) related to health and its determinants contain aspects of quality of life that clearly affect people’s physical or mental health. One of the newest ways to assess the health and also the quality of life-related to health is the self-assessed health of the individual. The aim of the present study was assessment of unhealthy days, self-reported health status, and its influencing factors on residents of the marginalpart of Mashhad, Iran. Methods: In the current cross-sectional study, 580 citizens of the marginal regions and slum areas of Mashhad city were enrolled through cluster sampling method using governmental health care services divisions. The Persian version of the questionnaire CDC HRQOL-4 was used to measure the unhealthy days. Data was analyzed using SPSS, version 11.5, running ANOVA, chi-square, and t-tests. P-value of less than 0.05 was considered as statistically significant. Results: In the present study, 359 persons (61%) were women and the mean age of participants was 32.6±11.51 years. The means of unhealthy days, physically unhealthy days, mentally unhealthy days, and days with dysfunction were found to be 7.2, 2.8, 4.1, and 1.7 days, respectively. The unhealthiest days (physical and mental) were seen in unemployed people and the best to excellent health days were seen in housewives. Conclusion: Unhealthy days and days with dysfunction were reported higher in slum inhabitants, especially female, low literacy, and housewife participants. Providing the education and employment facilities for people who live in marginal city areas might decrease the unhealthy days. Keywords: Unhealthy days; Health; Urban Marginal Inhabitants; Mashhad